Prevalence, Risk Factors, and Clinical Characteristics of Lipodystrophy in Insulin-Treated Patients with Diabetes: An Old Problem in a New Era of Modern Insulin - Thewjitcharoen Y (Dove Medical Press, 2020)
Yotsapon Thewjitcharoen,1 Hussamon Prasartkaew,1 Phatharaporn Tongsumrit,1 Saruda Wongjom,1 Chatnapa Boonchoo,1 Siriwan Butadej,1 Soontaree Nakasatien,1 Krittadhee Karndumri,1 Veekij Veerasomboonsin,2 Sirinate Krittiyawong,1 Thep Himathongkam1 1Diabetes and Thyroid Center, Theptarin Hospital, Bangkok, Thailand; 2Department of Radiology, Theptarin Hospital, Bangkok, ThailandCorrespondence: Yotsapon ThewjitcharoenDiabetes and Thyroid Center, Theptarin Hospital, Bangkok, ThailandTel +66-2-348-7000Email kamijoa@hotmail.comBackground: Lipodystrophy has been reported as a common complication in insulin-treated patients, which could lead to unexplained hypoglycemia and suboptimal glycemic control. This study aimed to determine the prevalence, associated risk factors, and clinical characteristics of insulin-induced lipodystrophy in Thai patients.Patients and Methods: This was a cross-sectional study involving insulin-treated patients at Theptarin Hospital, one of the largest diabetes centers in Thailand.Results: A total of 400 patients were studied (female 53.5%, T2DM 86%, mean age 65.6± 15.4 years, duration of diabetes 23.0± 10.2 years, median insulin treatment 10 years, usage of insulin analog 72.1%, A1C 7.9± 1.6%) . The prevalence of lipohypertrophy (LH) in overall patients was 37.3% (T1DM 46.4% and T2DM 35.8%). The highest prevalence (57.5%) was observed in long-standing (≥ 10 years) T1DM patients. Multivariate analysis revealed that the duration of insulin use (≥ 10 years), use of human insulin, and incorrect rotation of injection sites were associated with LH. Patients with LH were found to have 7-times greater risk of unexplained hypoglycemia when compared with patients without LH. Lipoatrophy (LA) was found in only four cases (1.0%). All LA cases had a concurrence palpable area of LH.Conclusion: Insulin-induced lipodystrophy is still an overlooked complication in the conundrum of diabetes care. The presence of lipodystrophy was significantly associated with the occurrence of unexplained hypoglycemia. It should be emphasized to recognize this condition by inspecting and palpating insulin injecting sites regularly, and educate patients to avoid the development of lipodystrophy.Keywords: lipodystrophy, lipohypertrophy, lipoatrophy, insulin, Thai